2018
DOI: 10.1093/pcp/pcy034
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptor Homolog3.4 is Involved in Regulation of Seed Germination Under Salt Stress in Arabidopsis

Abstract: Seed germination is sensitive to salt stress. ABA and Ca2+ are involved in the regulation of seed germination under salt stress. Ca2+ influx mediated by glutamate receptors (GLRs) plays important roles in many physiological processes in plants. Here, we investigated the correlation of GLRs, Ca2+ and ABA during seed germination in response to salt stress by using Arabidopsis thaliana wild-type and T-DNA insertion knockout mutants of glutamate receptor homolog3.4. We demonstrated that atglr3.4-1 and atglr3.4-2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 46 publications
2
56
0
Order By: Relevance
“…As discussed above, seed germination is sensitive and fragile to environmental stress including NaCl stress, and Ca 2+ and ABA regulate seed germination under NaCl stress. In A. thaliana, the results of Cheng et al (2018) showed that, compared with the wild-type plants, the AtGLR3.4-1 and AtGLR3.4-2 mutant plants were more sensitive to NaCl in both seed germination and postgermination seedling growth. In addition, in wild-type seedlings, NaCl triggered a striking increase in [Ca 2+ ] cyt , but this increase was blocked by DNQX (GLR antagonist); whereas in both AtGLR3.4-1 and AtGLR3.4-2 mutants NaCl-triggered increase in [Ca 2+ ] cyt was impaired (Cheng et al, 2018).…”
Section: Salt Stressmentioning
confidence: 98%
See 2 more Smart Citations
“…As discussed above, seed germination is sensitive and fragile to environmental stress including NaCl stress, and Ca 2+ and ABA regulate seed germination under NaCl stress. In A. thaliana, the results of Cheng et al (2018) showed that, compared with the wild-type plants, the AtGLR3.4-1 and AtGLR3.4-2 mutant plants were more sensitive to NaCl in both seed germination and postgermination seedling growth. In addition, in wild-type seedlings, NaCl triggered a striking increase in [Ca 2+ ] cyt , but this increase was blocked by DNQX (GLR antagonist); whereas in both AtGLR3.4-1 and AtGLR3.4-2 mutants NaCl-triggered increase in [Ca 2+ ] cyt was impaired (Cheng et al, 2018).…”
Section: Salt Stressmentioning
confidence: 98%
“…In A. thaliana, the results of Cheng et al (2018) showed that, compared with the wild-type plants, the AtGLR3.4-1 and AtGLR3.4-2 mutant plants were more sensitive to NaCl in both seed germination and postgermination seedling growth. In addition, in wild-type seedlings, NaCl triggered a striking increase in [Ca 2+ ] cyt , but this increase was blocked by DNQX (GLR antagonist); whereas in both AtGLR3.4-1 and AtGLR3.4-2 mutants NaCl-triggered increase in [Ca 2+ ] cyt was impaired (Cheng et al, 2018). Also, under NaCl stress, both mutants showed a lower expression of salt overly sensitive (SOS3), SOS2, and SOS1, as well as more accumulation of Na + than wild-type seeds (Cheng et al, 2018).…”
Section: Salt Stressmentioning
confidence: 98%
See 1 more Smart Citation
“…AtGLR3.4 and AtGLR3.5, two Ca 2+ -permeable channels belonging to the GLR family, have a dual localization, at the plasma membrane and chloroplasts the former (Teardo et al, 2010;Teardo et al, 2011), in mitochondria and chloroplasts the latter (Teardo et al, 2015). Both seem to play a role in ABA signaling under abiotic stress (Cheng et al, 2018;Ju et al, 2020), although their direct involvement in organellar Ca 2+ signaling under abiotic stress has to be investigated more in depth.…”
Section: Current Knowledge Of the Molecular Players Involved In Ca 2+mentioning
confidence: 99%
“…In recent years, increasing research attention has been paid to salt stress that can affect the growth and development of plants, especially in the stage of seed germination [1,2]. The response of plants to salt stress is complex, which is achieved through a variety of physiological and biochemical reactions and molecular mechanisms, and also involves the differential expression of stress-related genes in the corresponding pathways [3][4][5].…”
Section: Introductionmentioning
confidence: 99%